Antitumor and Immunomodulatory Effects of Polysaccharides from Broken-Spore of Ganoderma lucidum - Wang, Peng-Yun; Zhu, Xiao-Ling; Lin, Zhi-Bin (Frontiers in Pharmacology, 2012)
The antitumor and immunomodulatory activity of broken-spore of Ganodermalucidum polysaccharides (Gl-BSP) were investigated in vivo and in vitro. It was showed that Gl-BSP (50, 100, and 200 mg kg−1) exhibited antitumor effect against Sarcoma 180 (S180) in BALB/c mice. The Gl-BSP was not cytotoxicity in S180 cells and PG cells (human lung carcinoma cell) in vitro. However, serum from Gl-BSP-treated S180-bearing mice significantly inhibited S180 and PG cells proliferation in vitro. Moreover, Gl-BSP promoted the splenic lymphocyte proliferation induced by Con A or LPS, enhanced nature killer cell (NK cell) cytotoxic activity, augmented the percentage of neutral red phagocytosis by macrophages, and increased the percentage of the CD4+ or CD8+ subset in S180-bearing mice. The serum level of IFN-γ, TNF-α, and nitric oxide was increased by Gl-BSP. Gl-BSP also showed immunomodulatory activities in tumor-bearing mice. Furthermore, neutralization with anti-TNF-α and/or anti-IFN-γ significantly diminished growth inhibition induced by Gl-BSP-treated serum of S180-bearing mice in S180 or PG cells. These observations suggest that the antitumor activity of Gl-BSP may be mainly related to the activation of the immune response of the host organism by the stimulation of NK cells, T cells, and macrophages.